Diet rich in date palm fruits improves memory, learning and reduces beta amyloid in transgenic mouse model of Alzheimer′s disease - Selvaraju Subash; Musthafa Mohamed Essa; Nady Braidy; Kathyia Awlad-Thani; Ragini Vaishnav; Samir Al-Adawi; Abdullah Al-Asmi; Gilles J Guillemin (Journal of Ayurveda and Integrative Medicine, 2015)
Background: At present, the treatment options available to delay the onset or slow down the progression of Alzheimer′s disease (AD) are not effective. Recent studies have suggested that diet and lifestyle factors may represent protective strategies to minimize the risk of developing AD. Date palm fruits are a good source of dietary fiber and are rich in total phenolics and natural antioxidants, such as anthocyanins, ferulic acid, protocatechuic acid and caffeic acid. These polyphenolic compounds have been shown to be neuroprotective in different model systems. Objective: We investigated whether dietary supplementation with 2% and 4% date palm fruits (grown in Oman) could reduce cognitive and behavioral deficits in a transgenic mouse model for AD (amyloid precursor protein [APPsw]/Tg2576). Materials and Methods: The experimental groups of APP-transgenic mice from the age of 4 months were fed custom-mix diets (pellets) containing 2% and 4% date fruits. We assessed spatial memory and learning ability, psychomotor coordination, and anxiety-related behavior in all the animals at the age of 4 months and after 14 months of treatment using the Morris water maze test, rota-rod test, elevated plus maze test, and open-field test. We have also analyzed the levels of amyloid beta (Aβ) protein (1-40 and 1-42) in plasma of control and experimental animals. Results: Standard diet-fed Tg mice showed significant memory deficits, increased anxiety-related behavior, and severe impairment in spatial learning ability, position discrimination learning ability and motor coordination when compared to wild-type on the same diet and Tg mice fed 2% and 4% date supplementation at the age of 18 months. The levels of both Aβ proteins were significantly lowered in date fruits supplemented groups than the Tg mice without the diet supplement. The neuroprotective effect offered by 4% date fruits diet to AD mice is higher than 2% date fruits diet. Conclusions: Our results suggest that date fruits dietary supplementation may have beneficial effects in lowering the risk, delaying the onset or slowing down the progression of AD.